Estilhaços do Espelho: o Jornal Arquitectos (1981-2015) como território da construção do arquitecto - Vitor Manuel Oliveira Alves (2021)
This dissertation explores the condition of the architect as a "being" in project and how his construction can be produced in relation with an "other" reflected in the printed pages of Jornal Arquitectos (JA). The suspicion cast by Beatriz Colomina that Le Corbusier's "architectural self" was only possible through the printed media, opens the way for the hypothesis that this is a territory, but certainly not the only one, where, under ideal circumstances, any architect can build his "self" and become a "Subject". In this sense, the JA, due to the particular place it occupies among specialized periodicals in Portugal because of its longevity, number, capacity for its renewal and specific audience, proves to be not only a sensitive witness to variations of those constitutive processes but also an active agent in its production. Here, it is analysed as a "mirror" (Jacques Lacan) in which authors and readers can identify themselves with the image reflected in their pages in order to form their "self"; as an "apparatus" (Michel Foucault) that manages the relations of force and power that control disciplinary knowledge and discursive practices that transform the individual into a "Subject"; and where architects "perform" (Judith Butler) through a sustained set of significant acts that promote their constitution. These are the conceptual tools that helped the full reading of all articles and projects published by JA until the number 252, seeking to identify, in each series, which images of the architect they produce, how they are represented and what are their supposed constitutive imperatives. In parallel, the categorization of the published elements and their organization in diagrams clarify the reasons for these interpretations, allowing, in the same way, to dismantle certain "myths" that deformed, in a "natural" and unified image, what is an architect in post-modernity, necessarily unfinished, fragmented and plural. The author's name is a possibility for the longed-for, but temporary, stability, as well as the body produced as a manifestation of a discourse that gives it its material consistency and a meaning, also temporary and contingent. The existence of an "I-architect" created from the fundamental matrix shaped by different lines of force from the published authors, conceiving an image of a kind of "ideal-I" sufficiently stable for the identification process to occur, and the "Subject-architect" as a result of power relations, through a discourse and regulatory schemes conditioned by the cultural context in which it is inserted, or which has as a referent, and realized through performative action, are hypotheses that explain the construction of the architect.